Multifunctional nanoplatform based on star-shaped copolymer for liver cancer targeting therapy - Xianling Gong; Yi Zheng; Guangzhi He; Kebing Chen; Xiaowei Zeng; Zhihong Chen (Taylor & Francis Group, 2019)
With high morbidity and death rates, liver cancer has become one of the most common cancers in the world. But, most chemotherapeutic anticancer drugs have high toxicity as well as low specificity. To improve the treatment modalities and enhance the therapeutic effect of liver cancer, a brand new liver-targeting nanoparticle (NP), Ent-11α-hydroxy-15-oxo-kaur-16-en-19-oic acid (5 F)-loaded cholic acid (CA)-functionalized star-shaped poly (lactic-co-glycolic acid) (PLGA)-polyethylene glycol (PEG)-lactobionic acid (LA) (5 F-loaded CA-PLGA-PEG-LA), was developed. The particle size, zeta potential, size distribution, surface morphology, drug loading content, drug encapsulation efficiency and drug release of 5 F-loaded NPs were characterized. Confocal microscopy and flow cytometry showed that the prepared NPs could be internalized by HepG2 cells. Furthermore, the cellular uptake efficiency of coumarin 6-loaded CA-PLGA-PEG-LA NPs was much better in compare with that of CA-PLGA-PEG and CA-PLGA NPs. Moreover, LA-conjugated NPs (CA-PLGA-PEG-LA NPs) enhanced fluorescence of HepG2 cells via ligand-mediated endocytosis. The antitumor effects of 5 F-loaded NPs were evaluated by the MTT assay in vitro and by a xenograft tumor model in vivo, demonstrating that targeted 5 F-loaded CA-PLGA-PEG-LA NPs were significantly superior to free 5 F and 5 F-loaded CA-PLGA-PEG NPs. All the results indicated the 5 F-loaded CA-PLGA-PEG-LA NPs can be employed as a novel potentially targeting drug delivery system for liver cancer therapy.